Self-Assembled Monolayers for Dental Implants (2018)
Implant-based therapy is a mature approach to recover the health conditions of patients affected by edentulism. Thousands of dental implants are placed each year since their introduction in the 80s. However, implantology faces challenges that require more research strategies such as new support therapies for a world population with a continuous increase of life expectancy, to control periodontal status and new bioactive surfaces for implants. The present review is focused on self-assembled monolayers (SAMs) for dental implant materials as a nanoscale-processing approach to modify titanium surfaces. SAMs represent an easy, accurate, and precise approach to modify surface properties. These are stable, well-defined, and well-organized organic structures that allow to control the chemical properties of the interface at the molecular scale. The ability to control the composition and properties of SAMs precisely through synthesis (i.e., the synthetic chemistry of organic compounds with a wide range of functional groups is well established and in general very simple, being commercially available), combined with the simple methods to pattern their functional groups on complex geometry appliances, makes them a good system for fundamental studies regarding the interaction between surfaces, proteins, and cells, as well as to engineering surfaces in order to develop new biomaterials.